Controlling the Flashpoint of a Flammable Solvent with a Refrigerant - Fu, Yinchi; Lu, Jiaji; Wang, Tianrun; Cao, Helen; Ma, Tingguang (Fire technology, 2022)
The transportation industry demands the flammability control in the safe transportation of any liquid mixtures. Here the flashpoint of a flammable solvent is controlled by adding an evaporative diluent into the mixture. The flashpoint of this binary mixture is predictable with the help of Method of Flammable Resistance. Here methanol and heptane were chosen as typical fuels to be tested while R141b and R1233zd were added to control the flashpoint. Experimental results show that the binary mixture demonstrated the predicted behavior with the help of a new modeling scheme for mixing and the activity models for non-ideal evaporation. This methodology has the potential for predicting the flashpoint of any combinations of solvents, though some kind of synergistic behavior may appear when small fraction of a diluent is involved.